1999
DOI: 10.1007/bf02561617
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic polyurethane—The material used for the erlanger silver catheter

Abstract: The Erlanger silver catheter consists of a thermoplastic polyurethane elastomer (TPU). To achieve an antimicrobial effect, silver particles at a concentration of 0.5-1.0% by weight are incorporated into the basic material. The good mechanical properties were shown to remain present after the incorporation of the silver. The characteristic mechanical data of blends made of a soft and a hard TPU type approximated closely to a linear relationship with the ratio of the mixture. The buckling stability of catheters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Thermoplastic polyurethane (TPU) is a biocompatible and biodegradable elastomer that has been approved by the FDA, and has been widely applied in biomedical science [ 9 , 10 ]. It has been reported that TPU can be used for catheters, vascular grafts and drug delivery carriers [ 11 13 ]. Moreover, TPU also exhibits remarkable chemical stability and good mechanical properties [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thermoplastic polyurethane (TPU) is a biocompatible and biodegradable elastomer that has been approved by the FDA, and has been widely applied in biomedical science [ 9 , 10 ]. It has been reported that TPU can be used for catheters, vascular grafts and drug delivery carriers [ 11 13 ]. Moreover, TPU also exhibits remarkable chemical stability and good mechanical properties [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioresorbable PU scaffolds have attracted considerable attention and their great potential in tissue engineering has been reported [28,29]. Thermoplastic polyurethane (TPU) as a class of PU has been widely employed in medical applications due to its biocompatibility and flexibility, and has been used in medical devices such as catheters [30], pace-maker leads [31], skin [32], and vascular grafts [33]. TPUs offer high elongation, moderate tensile strength and Young’s modulus, and excellent abrasion and tear resistance [34].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, zeolites have attracted interest for biomedical applications, including antidiarrheal agents, hemorrhage control, detoxicants, and antibacterial agents 10. In different applications, antibacterial PU is obtained by either the coating of PU with silver13, 14 or by silver particle impregnation 15–18. Using silver‐ion‐loaded zeolites as antibacterial agents offers an advantage over the other methods because silver ions are more effective than metallic silver atoms.…”
Section: Introductionmentioning
confidence: 99%